INCREASING POETRY WRITING SKILLS THROUGH QUANTUM WRITING METHOD IN CLASS X STUDENTS - Haoliya Haoliya; Sitti Rabiah; Nurfathana Mazhud (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This action research aims to improve the poetry writing skills of SMA Negeri 5 Makassar students through a quantum writing approach. This research was conducted using data collection instruments, namely tests and non-tests. The data analysis technique used is qualitative data analysis and quantitative data analysis. Qualitative data analysis technique is done by comparing student progress between before and after the cycle takes place based on the results of writing poetry. The improvement of poetry writing skills can be seen from the process and student learning outcomes. The results showed that the results showed that there was an increase in poetry writing skills in class X MIPA 1. The results of the initial test showed that students were less successful in interpreting poetry with an average score of 56.91%, after treatment in the first cycle there was an increase. of 71.58 the first cycle. Based on the development of the second cycle, the researchers continued the second cycle of treatment so that learning outcomes experienced a significant increase, namely 84.52%. Based on the results of the study, it can be concluded that the influence of the quantum writing method can increase students' poetry writing skills in class X SMA Negeri 5 Makassar in writing poetry.